A qualitative study examining the presence and consequences of moral framings in patients' and mental health workers' experiences of community treatment orders. Issue 1 (December 2015) - Lawn, Sharon; Delany, Toni; Pulvirenti, Mariastella; Smith, Ann; McMillan, John
Abstract Background Mental health recovery involves acknowledging the importance of building the person's capacity for agency. This might be particularly important for patients on community treatment orders (CTOs - which involve enforced treatment for their mental illness), given limited international evidence for their effectiveness and underlying concerns about the use of coercion by workers and systems of care towards this population of people with mental illness. Methods This study sought to understand how the meaning of CTOs is constructed and experienced, from the perspective of patients on CTOs and workers directly administering CTOs. Qualitative interviews were conducted with South Australian community mental health patients (n = 8) and mental health workers (n = 10) in 2013–14. During thematic analysis of data, assisted by NVIVO software, the researchers were struck by the language used by both groups of participants and so undertook an examination of the moral framings apparent within the data. Results Moral framing was apparent in participants' constructions and evaluations of the CTO experience as positive, negative or justifiable. Most patient participants appeared to use moral framing to: try to understand why they were placed on a CTO; make sense of the experience of being on a CTO; and convey the lessons they have learnt. Worker participants appeared to use moral framing to justify the imposition of care. Empathy was part of this, as was patients' positive right to services and treatment, which they believed would only occur for these patients via a CTO. Workers positioned themselves as trying to put themselves in the patients' shoes as a way of acting virtuously towards them, softening the coercive stick approach. Four themes were identified: explicit moral framing; best interests of the patient; lessons learned by the patient; and, empathy. Conclusions Experiences of CTOs are multi-layered, and depend critically upon empathy and reflection on the relationship between what is done and how it is done. This includes explicit examination of the moral framing present in everyday interactions between mental health workers and their patients in order to overcome the paradox of the moral grey zone between caring and controlling. It suggests a need for workers to receive ongoing empathy training.